Determining Golf Swing Patterns Using Motion Sensors for Injury Prevention - Tangwongcharoen, Wisan; Titiroongruang, Wisut (My University, 2017)
Golf is a popular sport for exercise or socializing. It affects an increasing number of patients. Because of these reasons the researchers decided to focus on this problem. We presented the analysis golf swing using sensors named Razor IMU to detect golf swing motions. The rotation and acceleration data were gathered by sensors attached on the upper and lower back. These data were clustered by K-Mean Clustering. The data clusters were calculated boundaries by Z-Score. The normal and abnormal data were compared for the Back Swing-Half Swing to Top Swing position and Top Swing to impact position. From the experimental results, this algorithm can classify normal and abnormal data due to the significant differences. This paper can help to improve and correct swings and thus avoid injuries.
Keywords: Accelerometer; Golf Swing Pattern; Gyroscope; Injury Prevention; K-Mean Clustering; Polar Coordinate System; Standard Score